Altered lipid metabolism in synovial fibroblasts of individuals at risk of developing rheumatoid arthritis. Issue 134 (January 2023) - de Jong, T.A.; Semmelink, J.F.; Denis, S.W.; van de Sande, M.G.H.; Houtkooper, R.H.L.; van Baarsen, L.G.M.
Abstract: Objective: Fibroblast-like synoviocytes (FLS) can augment the inflammatory process observed in synovium of patients with rheumatoid arthritis (RA). A recent transcriptomic study in synovial biopsies revealed changes in metabolic pathways before disease onset in absence of synovial tissue inflammation. This raises the question whether alterations in cellular metabolism in tissue resident FLS underlie disease pathogenesis. Materials and methods: To study this, we compared the metabolic profile of FLS isolated from synovial biopsies from individuals with arthralgia who were autoantibody positive but without any evidence of arthritis (RA-risk individuals, n = 6) with FLS from patients with RA (n = 6), osteoarthritis (OA, n = 6) and seronegative controls (n = 6). After synovial digestion, FLS were cultured in vitro and cellular metabolism was assessed using quantitative PCR, flow cytometry, XFe96 Seahorse Analyzer and tritium-labelled oleate oxidation assays. Results: Real-time metabolic profiling revealed that basal (p < 0.0001) and maximum mitochondrial respiration (p = 0.0024) were significantly lower in RA FLS compared with control FLS. In all donors, basal respiration was largely dependent on fatty acid oxidation while glucose was only highly used by FLS from RA patients. Moreover, we showed that RA-risk and RA FLS are less metabolically flexible. Strikingly, mitochondrial fatty acid β-oxidation was significantly impaired in RA-risk (p = 0.001) and RA FLS (p < 0.0001) compared with control FLS. Conclusion: Overall, this study showed several metabolic alterations in FLS even in absence of synovial inflammation, suggesting that these alterations already start before clinical manifestation of disease and may drive disease pathogenesis. Highlights: Synovial fibroblasts (FLS) display metabolic alterations before onset of RA. Lower basal and maximum mitochondrial respiration in RA FLS compared with controls. Control FLS are more flexible to increase metabolic pathway oxidation. Fatty acid β-oxidation is significantly impaired in RA-risk and RA FLS. FLS mitochondria might be attractive drug targets aimed at halting disease progression.